Near-source seismic demand and pulse-like records A discussion for L'Aquila earthquake. - Chioccarelli, Eugenio
Rupture directivity effects in ground motion are known since many years to both seismologists and earthquake engineers, i.e. in sites that are in a particular geometrical configuration with respect to the rupture, the velocity fault-normal signals may show a large pulse which occurs at the beginning of the record and contains the most of energy. The results are waveforms different from ordinary ground motions recorded in the far field or in geometrical conditions not favorable with respect to directivity. Current attenuation laws are not able to capture such effect well, if at all, and current probabilistic seismic hazard analysis is not able to predict the resulting peculiar spectral shape. Moreover, it is believed that structures with dynamic behavior in a range of periods related to the pulse period may be subjected to underestimated seismic demand. In the paper this is investigated and increments in both elastic and inelastic seismic actions are quantified using a large dataset of records, from the next generation attenuation project (NGA), in which a fraction is comprised of velocity pulses identified in other studies. These analyses employ recently developed tools and procedures to assess directivity effects and to quantify the associated threat in terms of seismic action on structures. Subsequently, the same tools are used in one of the first attempts to identify near-source effects in the data recorded during a normal faulting earthquake, the mainshock of the recent Abruzzo (central Italy) sequence, leading to conclude that pulse-like effects are likely to have occurred in the event, that is (1) observation of pulse-like records in some near-source stations is in fair agreement with existing predictive models, (2) the increment in seismic demand shown by pulse-like ground motion components complies with the results of the analysis of the NGA data, and (3) seismic demand in non-impulsive recordings is generally similar to what expected for ordinary records. The results may be useful as a benchmark for inclusion of near-source effect in design values of seismic action and structural risk analysis.
Keywords: Ground motion; Seismic hazard; Seismic action; Near-source.; Directivity